On wings of blood - Boleyn, Briar (Boleyn, Briar. Bloodwing Academy, 2025)
I didn't sign up for this. A half-fae in a school of highblood vampires? That's a recipe for suffering. I'm Medra Pendragon, last of the dragon riders -- or so they tell me. Funny thing is, there are no dragons left. Not a single one. But somehow, that hasn't stopped the vampires from deciding I'm worth capturing. Now I'm stuck at Bloodwing Academy, where the highbloods run everything, and blightborn like me? We're just blood in their veins, pawns in their games. But that's not even the worst part. Enter Blake Drakharrow: cold, arrogant, and way too gorgeous for his own good. He's been tormenting me since the moment we met, and now, thanks to some ancient ritual, we're betrothed. He acts like he owns me, but I'm not going down without a fight. Bloodwing isn't just a school -- it's a battlefield. Highbloods fight for power, and if you're weak, you're dead.